Pemberdayaan Petani Paprika melalui Program CSR: Studi Kasus Kelompok Tani Tunas Tani Pangrango - Rival Fairuz; Widiyanto Widiyanto; Dwiningtyas Padmaningrum (AGRITEXTS: Journal of Agricultural Extension, 2026)
Corporate Social Responsibility (CSR) programs are an effective strategy for empowering farmers, particularly in the horticultural sector. In practice, few CSR programs focus on farmer empowerment, underscoring the need for a study on how community-oriented CSR programs can synergize with a company's business objectives. This study aims to examine the process and impact of empowering paprika farmers through Pizza Hut Indonesia's CSR program within the Tunas Tani Pangrango Farmers Group in Bogor. The study was conducted from August 2024 to May 2025. Using a qualitative case study approach, data were collected through interviews with 13 informants, observation, and documentation. The results show that the empowerment process involves strategy identification, group development, participatory planning, activity implementation, and joint monitoring and evaluation. The program has had a positive impact on farmers' productivity, income, technical capacity, and market access. Socially, institutional strengthening and collective learning among farmers have occurred. However, challenges remain in the environmental aspect, particularly the use of chemical pesticides. It can be concluded that Pizza Hut Indonesia's CSR program increases farmer empowerment and encourages independent farming businesses, but it should pay greater attention to environmental sustainability by using environmentally friendly inputs and adopting sustainable cultivation technologies. This study found: (1) integration of extension, training, research, and supporting subsystems (agricultural facilities and markets) in Pizza Hut Indonesia's CSR program in Agricultural Knowledge and Information Systems; and (2) empirical evidence that with a community empowerment approach, CSR program obligations are able to synergize with the company's business mission.